Admission Source Is Associated With the Risk of Rapid Response Team Activation in a Children's Hospital. - Kamzan, Audrey D.; Tsoi, Stephanie; Arslanian, Talin; Myung Shin Sim; Romero, Tahmineh; Newcomer, Charles A. (Academic Pediatrics)
Objective: To evaluate source of admission to a children's hospital as a predictor of rapid response team (RRT) activation, both in the first 48 hours of admission and over the entire hospitalization. METHODS: Retrospective cohort study of all patients admitted to the pediatric ward between March 1, 2013 and December 31, 2015. Source of admission was categorized as from the emergency department, transfer from another hospital facility, admission following a planned surgery, direct admission planned in advance, or unplanned direct admission. Information was collected including whether or not the patient had a RRT activation and survival to discharge. A Fisher's exact test was used to assess the association between source of admission and risk of rapid response. Results: Of 8083 admissions included in the study, 194 had at least one RRT event. The odds of having an RRT was significantly associated with source of admission (P < .001). Using admission from the emergency department as a reference group. planned elective admissions (odds ratio [OR] 0.27: P < .001) and admissions following planned surgery (OR 0.07: P < .001) were significantly associated with reduced odds of having at least one RRT activation during the admission. Planned elective admissions also demonstrated reduced odds of RRT in the first 48 hours of hospitalization (OR 0.14: P = .002). Source of admission was also associated with sun rival to discharge (P < .05). Conclusion: Source of admission is associated with likelihood of RRT activation as well as with survival to discharge and should be considered by providers when assessing inpatient risk of decompensation.